What can gaze behaviors, neuroimaging data, and test scores tell us about test method effects and cognitive load in listening assessments?. (January 2022) - Aryadoust, Vahid; Foo, Stacy; Ng, Li Ying
The aim of this study was to investigate how test methods affect listening test takers' performance and cognitive load. Test methods were defined and operationalized as while-listening performance (WLP) and post-listening performance (PLP) formats. To achieve the goal of the study, we examined test takers' ( N = 80) brain activity patterns (measured by functional near-infrared spectroscopy (fNIRS)), gaze behaviors (measured by eye-tracking), and listening performance (measured by test scores) across the two test methods. We found that the test takers displayed lower activity levels across brain regions supporting comprehension during the WLP tests relative to the PLP tests. Additionally, the gaze behavioral patterns exhibited during the WLP tests suggested that the test takers adopted keyword matching and "shallow listening." Together, the neuroimaging and gaze behavioral data indicated that the WLP tests imposed a lower cognitive load on the test takers than the PLP tests. However, the test takers performed better with higher test scores for one of two WLP tests compared with the PLP tests. By incorporating eye-tracking and neuroimaging in this exploration, this study has advanced the current knowledge on cognitive load and the impact imposed by different listening test methods. To advance our knowledge of test validity, other researchers could adopt our research protocol and focus on extending the test method framework used in this study.